Personality Characteristics of Introvert, Extrovert, and Ambivert in Elementary School Students - Fitri, Rila Melyana; Toharudin, Moh; Bahrulinnisa, Fia (Pedagogik Journal of Islamic Elementary School, 2022)
The purpose of this study is to describe the character and personality of the first and third graders of SDIT Nurul Hidayah Brebes. This research uses a case study qualitative method, data collection by non-participant observation and a literature study. The validity of the data used using source triangulation. Then the data were analyzed through data reduction and conclusion. The results of this study are three personal students at SDIT Nurul Hidayah, namely individuals who tend to be closed. These students prefer their world and tranquillity; quiet students have open personalities, prefer the outside world and constantly interact with their friends, and have flexible personalities, whereas these students have an open and sometimes closed character.